2022
DOI: 10.1161/strokeaha.121.036139
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Management After Intracerebral and Subarachnoid Hemorrhage: The Knowns and Known Unknowns

Abstract: Blood pressure (BP) elevations often complicate the management of intracerebral hemorrhage and aneurysmal subarachnoid hemorrhage, the most serious forms of acute stroke. Despite consensus on potential benefits of BP lowering in the acute phase of intracerebral hemorrhage, controversies persist over the timing, mechanisms, and approaches to treatment. BP control is even more complex for subarachnoid hemorrhage, where there are rationales for both BP lowering and elevation in reducing the risks of rebleeding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…The importance of striking a balance between the prevention of rebleeding and the avoidance of secondary cerebral ischemia is highlighted, especially during the initial treatment (Ma and Bebawy, 2022). However, there is disagreement about the target blood pressure threshold (Steiner et al, 2013;Minhas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of striking a balance between the prevention of rebleeding and the avoidance of secondary cerebral ischemia is highlighted, especially during the initial treatment (Ma and Bebawy, 2022). However, there is disagreement about the target blood pressure threshold (Steiner et al, 2013;Minhas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a recent study also confirmed that the median age of patients was 74 (66-82) years for ischemic stroke, 70 (59-79) years for intracerebral hemorrhage, and 64 (53-75) years for subarachnoid hemorrhage among the 183,080 stroke patients [27]. Thus, younger patients who suspected stroke may have an increased risk of hemorrhagic stroke prehospital, which was associated with the poorer blood pressure control and an increased proportion of subarachnoid hemorrhage [28].…”
Section: Discussionmentioning
confidence: 77%
“…The first was on the current evidence, knowledge gaps, and emerging concepts on BP management after SAH and ICH and the second was on BP management in the first 24 hours after ischemic stroke. 56,57 The final one was on optimal hemodynamic parameters for brain-injured patients in the clinical setting. 58 Other interesting reviews include opioid alternatives in spine surgery, the effects of anesthesia on glioma progression and cardiac-cerebral coupling.…”
Section: Narrative Reviews Of Interestmentioning
confidence: 99%